Preserving the Integrity of Surfactant-Stabilized Microbubble Membranes for Localized Oxygen Delivery - Oeffinger, Brian E; Vaidya, Purva; Ayaz, Iman; Shraim, Rawan; Eisenbrey, John R; Wheatley, Margaret A (Langmuir, 2019)
Ultrasound contrast agents consist of stabilized microbubbles. We are developing a surfactant-stabilized microbubble platform with a shell composed of Span 60 (Sorbitan monostearate) and an emulsifying agent, water-soluble vitamin E (α-tocopheryl poly(ethylene glycol) succinate, abbreviated as TPGS), named SE61. The microbubbles act both as an imaging agent and a vehicle for delivering oxygen to hypoxic areas in tumors. For clinical use, it is important that a platform be stable under storage at room temperature. To accomplish this, a majority of biologicals are prepared as freeze-dried powders, which also eliminates the necessity of a cold chain. The interfaces among the surfactants, gas, and liquids are subject to disruption in both the freezing and drying phases. Using thermocouples to monitor temperature profiles, differential scanning calorimetry to determine the phase transitions, and acoustic properties to gauge the degree of microbubble disruption, the effects of the freezing rate and the addition of different concentrations of lyoprotectants were determined. Slower cooling rates achieved by freezing the samples in a −20 °C bath were found to be reproducible and produce contrast agents with acceptable acoustical properties. The ionic strength of the solutions and the concentration of the lyoprotectant determined the glass-transition temperature (T g′) of the frozen sample, which determines at what temperature samples can be dried without collapse. Crucially, we found that the shelf stability of surfactant-shelled oxygen microbubbles can be enhanced by increasing the lyoprotectant (glucose) concentration from 1.8 to 5.0% (w/v), which prevents the melt temperature (T m) of the TPGS phase from rising above room temperature. The increase in glucose concentration results in a lowering of T m of the emulsifying agent, preventing a phase change in the liquid-crystalline phase and allowing for more stable bubbles. We believe that preventing this phase change is necessary to producing stabilized freeze-dried microbubbles.